2021
DOI: 10.1007/s42330-021-00149-3
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students’ Learning of Linear Algebra Through Mathematical Modelling Routes

Abstract: Mathematical modelling has acquired relevance at all educational levels in the last decades since integrating this activity in instruction provides significant contexts for improving students' learning, including in linear algebra courses that have a notable presence in many undergraduate courses from different fields, including engineering and sciences. This paper reports a study aiming to characterize the distinct modelling routes performed by Costa Rican undergraduate students when solving a mathematical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Checking and validating solutions obtained is another important mathematical activity that can be supported by digital technology. These considerations clearly show that digital technology can prove useful in different phases of the modelling process (Greefrath, 2011;Ramirez-Montes et al, 2021;Frenken et al, 2022). Figure 2 shows different ways of applying digital technology (in italics) within a modelling process in Blum and Leiß's (2007) sevenstep modelling cycle.…”
Section: Theoretical Framework On the Use Of Digital Technologies In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Checking and validating solutions obtained is another important mathematical activity that can be supported by digital technology. These considerations clearly show that digital technology can prove useful in different phases of the modelling process (Greefrath, 2011;Ramirez-Montes et al, 2021;Frenken et al, 2022). Figure 2 shows different ways of applying digital technology (in italics) within a modelling process in Blum and Leiß's (2007) sevenstep modelling cycle.…”
Section: Theoretical Framework On the Use Of Digital Technologies In ...mentioning
confidence: 99%
“…However, the use of technology may introduce challenges to the modelling process; for instance, technical glitches may generate some problems such as outdated web links and errors in a technological system (Merck et al, 2021). Ramirez-Montes et al (2021) reported that technology may not always support students' skills to complete all stages of the modelling cycle as technology may restrict the extensive route of modelling with the acquisition of computational results. For example, technology can support students in measurement and calculation processes, but not in interpretation of the results.…”
Section: Introductionmentioning
confidence: 99%
“…Ramírez Montes et al (2021) focus their research on mathematical modeling, particularly involving the concept of solving a system of linear equations. They investigated the modeling competencies of undergraduate students in Costa Rica in linear algebra concepts.…”
Section: Douglas Mcdougallmentioning
confidence: 99%
“…Hernandez-Martinez & Vos, 2018). By looking at modelling tasks from different mathematics disciplines, several potentials for the development and training of mathematical thinking and acting can be recognized, too: Tasks require, for instance, discrete mathematics (e.g., Greefrath et al, 2022), algebraic structures (e.g., Ramírez-Montes et al, 2021) or geometric skills (e.g., A preliminary analysis of data concerning mathematical modelling was published in journal "Educational Studies in Mathematics" in March 2023. This paper extends this focus by providing a detailed analysis of encountered challenges.…”
Section: Introductionmentioning
confidence: 99%